Etika Qur’ani bagi Muslim Minoritas: Kajian QS. Al-An‘am 108 dan Al-Mumtahanah 8–9 - ulya, indi karimatul (Maliki Interdisciplinary Journal, 2026)
The discussion on Muslim minorities is increasingly relevant in today’s diverse societies, as their position requires the ability to build harmonious relationships with other groups while maintaining religious identity. Muslims living as minorities need a clear Islamic legal foundation that preserves their core beliefs and, at the same time, supports peaceful social interaction. This study examines the social-educational values reflected in QS. Al-An‘am:108 and QS. Al-Mumtahanah: 8–9. QS. Al-An‘am:108 emphasizes the prohibition against insulting the religious objects of others, as such actions may provoke harsher retaliation and disrupt social harmony. QS. Al-Mumtahanah:8 highlights that Islam permits kindness and justice toward non-Muslims who adopt a peaceful attitude toward Muslims. Conversely, QS. Al-Mumtahanah:9 sets boundaries by prohibiting close alliances with those who show hostility or expel Muslims from their land. The findings indicate that the Qur’an provides balanced guidance for Muslim minorities: promoting tolerance, justice, and ethical communication while maintaining caution toward potential threats. These values can serve as an ethical framework for shaping the social character of Muslim minorities in the modern era.